Integrated Landscape Management for Addressing Land Degradation, Food Security and Climate Resilience in The Bahamas - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2021)
IICA has been contracted to support the Department of Environmental Protection and Policy (DEPP) which is a unit of the Ministry of The Environment and Housing in The Bahamas with the implementation of a project preparation grant to develop a GEF Full-sized project "Integrated Landscape Management for Addressing Land Degradation, Food Security and Climate Resilience Challenges in The Bahamas". This preparatory phase will finalize studies and arrangements necessary for the submission of project documents to the GEF; undertake stakeholder consultations and data collection in order to facilitate participation; define relevant baseline and complementary activities; and develop the required documents for the submission to the GEF and UN Environment programme.